Implementación de un programa de estimulación temprana dirigido a los hijos e hijas de las madres trabajadoras del mercado central, cuya edad oscila entre los 2 a 24 meses. :implementación de un programa de estimulación temprana dirigido a los hijos e hijas de las madres trabajadoras del mercado central, cuya edad oscila entre los 2 a 24 meses, de octubre 2015 a marzo de 2016 - Benítez Ramos, Gabriela Elizabeth (2016)
The present project took place in the Central Market located in the city of Quito Ecuador. This process has been directed to the sons and daughters of working mothers of the Central Market, with ages between 2 to 24 months. The implementation of a program of early stimulation in this place rises from the need to provide care to the young children, those children accompanying their mothers each workday, those who stay in reduced work stations and un-stimulating environments. It should be stressed that in the first years of life the brain develops quickly thanks to the neural connections, but this depends the context where the child develops and the quantity of stimulation the child receives, for this reason I decided to make a program focused on developing of the types of behavior suggested by Arnol Gesell: motor, language, personal-social and adaptive. The children were grouped by age, to get a more organized work, resulting 6 work groups. Once implemented the project, was applied to children the Nelson´s Ortiz scale of development, to know their current status psycho-evolutionary, later followed of the made intervention, I did a re-evaluation applying the same scale, in order to compare and to know the results obtained.